Pengembangan Zonasi Eduwisata di Kawasan Pendidikan Institut Teknologi Sumatera (ITERA) untuk Mendukung Pariwisata Berkelanjutan - Mentari Pratami; Sahid Sahid; Asep Nurul Ajiid Mustofa; Muhammad Andhika Refaldy; Karima Zahrani Rahman (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Educational tourism (Eduwisata) is an activity where tourists travel in groups to a place with the main aim of gaining direct learning experience about the location they are visiting. The Sumatra Institute of Technology (ITERA) Educational Area has great potential to develop education-based tourism, with interesting locations such as Embung A, which is currently used by students and the community for sports, Botanical Gardens, Astronomical Observatories, and other potential that has not yet been fully exploited. maximum. Even though it has a lot of potential, the use of edutourism in the ITERA area is currently still centered on Embung A as a sports facility. Therefore, this research aims to develop educational tourism zoning within the Sumatra Institute of Technology so that tourists can enjoy educational tourism more easily and to prevent the concentration of activities in only one location. This zoning development also aims to facilitate policy determination in optimizing the potential of edutourism areas. Through analysis of land capabilities and suitability, this research will produce a zoning map of the edutourism area. With this zoning map, it is hoped that visitors can more easily access various educational tourism locations in ITERA, and educational tourism activities can be spread more evenly throughout the area. Apart from that, it is hoped that better management of the edutourism area can make ITERA a superior edutourism destination that not only provides an enjoyable learning experience for visitors, but also supports the development of education and research in the campus environment.